Analysis The Impact of Viral Marketing, Price, and Online Costumer Review On a Celebrity Endorser-Mediated Buy Decision On The TikTokShop App - Apsari, Sindi Salsa; Nugraha, Maulana Alip; Astuti, Ramlah puji (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This study aims to analyze the influence of three main factors, namely viral marketing, perceived prices, and online customer reviews, on purchasing decisions mediated by celebrity endorsers in the TikTok application. Design/methodology/approach: This research uses a quantitative approach by collecting data through surveys using questionnaires and literature studies. Data analysis using regression tests with the help of the SPSS program. Research Findings: The results showed that viral marketing, perceived price, and online customer reviews are important factors that can influence consumer purchasing decisions on the Tiktokshop application. Theoretical Contribution/Originality: A marketing strategy that combines these factors effectively can be the key to increasing sales and company competitiveness on the Tiktokshop platform. Keywords: viral marketing, perceived price, online customer review, purchase decision, celebrity endorser